Development of MgMnO3-δ as an oxygen carrier material for chemical looping combustion. (1st November 2018) - Hwang, Jong Ha; Baek, Jeom In; Ryu, Ho Jung; Sohn, Jung Min; Lee, Ki-Tae
Highlights: MgMnO3-δ has a defect cubic spinel structure. The redox reaction from MgMnO3-δ to (Mg, Mn)O is reversible and stable. The oxygen transfer capacity of MgMnO3-δ for 15% CH4 /CO2 is 8.74 wt% at 900 °C. No phase or structure changes or agglomeration occurred during the redox cycle. Abstract: Chemical looping combustion (CLC) is attracting attention as a promising technology for carbon dioxide separation. Oxygen carrier materials are the most important factor in determining the efficiency of CLC. In this paper, we present MgMnO3-δ with a defect cubic spinel structure as an oxygen carrier material with high efficiency, low cost, and stable properties. MgMnO3-δ has a non-stoichiometric oxygen content of MgMnO2.68 . The reduced composition of MgMnO3-δ in H2, CO, or CH4 is a complete solid solution of (Mg, Mn)O. The redox reaction from MgMnO3-δ to (Mg, Mn)O is reversible and stable. Interestingly, MgMnO3-δ also shows a chemical looping oxygen uncoupling (CLOU) phenomenon and is reduced to MgMn2 O4 and MgO in N2 at 900 °C. The oxygen transfer capacities of MgMnO3-δ under 15% H2 /N2, 15% CO/CO2, 15% CH4 /N2, and 15% CH4 /CO2 are 8.34, 8.56, 8.42, and 8.74 wt%, respectively, at 900 °C. The oxygen transfer capacity was well maintained during the 5th redox cycle. No phase or structure changes or agglomeration occurred as the redox cycle number increased. Moreover, MgMnO3-δ has a high tolerance to carbon deposition when used in CO or CH4 fuels.